Three new species of Calepitrimerus (Acari: Eriophyidae) from China - Xue, Xiao-Feng; Liu, Xin-Yu (Zootaxa, 2022)
The genus Calepitrimerus (Acari: Eriophyoidea) comprise more than 90 extant species. Most species infest angiosperms, while only five were reported from gymnosperms. Herein, we describe and illustrate three new species of the genus Calepitrimerus from China: two from angiosperms, C. huayanlingense sp. nov. on Ficus erecta (Moraceae), C. cryptocaryaer sp. nov. on Cryptocarya concinna (Lauraceae), and one from a gymnosperm, C. liuanense sp. nov. on Cryptomeria japonica (Cupressaceae). All new species were found vagrant on lower surfaces of their hosts’ leaves, albeit inducing no apparent symptom. A list of Calepitrimerus species in China is tabulated.